The effect of circadian rhythm changes on fetal and placental development (experimental study) - Gozeri, Ebru; Celik, Husnu; Ozercan, Ibrahim; Gurates, Bilgin; Polat, Sinan Aytac; Hanay, Fethi (Maghira & Maas Publications, 2008)
OBJECTIVE: To investigate the effect of circadian rhythm changes on fetal-placental development in pregnant rats. MATERIAL AN D METHOD: Pregnant rats were randomly allocated to 4 groups with 10 rats in each group. Group 1: 12 hours light 12 hours dark period (n: 10, Control Group); Group 2: 6 hours light 6 hours dark period (n: 10); Group 3: constant light group (n:10); Group 4: constant dark group (n:10). Rats were made to deliver by cesarean birth at the end of their pregnancy and their placenta, number and weight of the offspring, and placental histopathological changes were examined. FINDING: Fetal number in the constant dark group was found significant in comparison to constant light group (p < 0.01). Fetal weight in all groups with altered circadian rhythm was significantly lower than that in the control group (p < 0.01). The decrease in fetal weight was more evident in the constant light group than in the constant dark group (p < 0.01). Comparison of the histopathological findings of the placenta showed that placental edema, fibrin accumulation and leukocyte infiltration were significantly higher in constant light and constant dark groups than in other groups (p < 0.01). CONCLUSION: Circadian rhythm change in pregnancy adversely affects the fetal-placental development. More detailed studies are needed to clarify this mechanism.
Keywords: circadian rhythm changes; fetal-placental development